Psychological Effects of the Hybrid Work Revolution on Modern Workforce - Lekha, Haritha (Digital Repository of Theses - SSBM Geneva, 2023)
The COVID-19 pandemic has profoundly altered our working practices, leading to a significant shift toward hybrid employment. Employees have the option to work from home or in the office in a hybrid workplace. This arrangement has some advantages, like more flexibility and shorter commute times, but it also brings with it several new challenges. The psychological impact on workers is one of the most pressing issues. The purpose of this study is to investigate the mental health, and work-life balance, job satisfaction, and other psychological effects of hybrid workers. Organizations and policymakers will greatly benefit from this study's findings as they navigate the ever-evolving work landscape and strive to create employee-friendly hybrid workplaces.